Functions of the GABAergic system on serum LH concentrations in pre-pubertal Nellore heifers - Cardoso, Daniel; Cardoso, Rodolfo C.; Nogueira, Guilherme de Paula [UNESP] (Elsevier B.V., 2021)
This study was conducted to evaluate the luteinizing hormone (LH) secretion pattern after gamma-aminobutyric acid (GABA(A)) antagonist to determine the effects of the GABAergic system on LH secretion during reproductive maturation in pre-pubertal Nellore heifers. Nellore heifers (n = 10) were administered a picrotoxin injection of 0.18 mg/kg, i.v. Blood samples were collected every 15 min for 3 h at different developmental stages (8, 10, 14 and 17 mo of age). Plasma concentrations of LH were quantified using an RIA (sensitivity of 0.04 ng/mL and CV of 15 %). There was an interaction between treatment and age (P = 0.034). Picrotoxin-treated heifers had lesser (P <= 0.05) LH mean concentrations during a 3 h period at 10 and 17 mo of age compared to control heifers (P <= 0.05). Comparing the period before and after Picrotoxin injection in the same animals, there was a 33 % decrease in LH concentration at 8 mo of age (P = 0.0165). These results indicate the GABAergic system has a stimulatory function in inducing LH secretion in pre-pubertal Nellore heifers. These findings corroborate previous results that GABA increases GnRH/LH secretion in other species during the pre-pubertal period.
Keywords: Hypothalamus; Neuroendocrine; Picrotoxin; Puberty; Sexual maturation